NAVIGATING FORENSIC ACCOUNTING BEHAVIORAL INTENTIONS THROUGH THE FRAUD DEVIATION MODEL - Devi, Seema (International Journal of Research -GRANTHAALAYAH, 2025)
Fraud remains widespread in modern business. People who commit fraud often display warning signs through their behavior and actions, which can escalate to aggressive and violent conduct. Researchers have developed various theories to detect and prevent fraudulent behavior, with each theory having specific strengths and limitations depending on the situation. To better understand fraudulent conduct, researcher combined existing fraud theories with behavioral models from other fields to create the Fraud Deviation Model (FDM). This model was validated using Structural Equation Modeling (SEM). The research included primary data collected from 560 participants in India's National Capital Region, comprising registered internal auditors, external auditors, government auditors, and forensic auditors.